2011
DOI: 10.1016/j.pain.2011.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Influence from genetic variability on opioid use for cancer pain: A European genetic association study of 2294 cancer pain patients

Abstract: Cancer pain patients need variable opioid doses. Preclinical and clinical studies suggest that opioid efficacy is related to genetic variability. However, the studies have small samples, findings are not replicated, and several candidate genes have not been studied. Therefore, a study of genetic variability with opioid doses in a large population using a confirmatory validation population was warranted. We recruited 2294 adult European patients using a World Health Organization (WHO) step III opioid and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
199
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(205 citation statements)
references
References 38 publications
6
199
0
Order By: Relevance
“…A total of 2,294 patients with cancer were recruited in the international, multicenter, cross-sectional EPOS [27], with the principal aim to examine the association between genetic variations and opioid efficacy on cancer pain relief. Patients were eligible if they had verified malignant disease, were aged $18 years, and were scheduled with opioid treatment for moderate to severe pain for at least 3 days.…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2,294 patients with cancer were recruited in the international, multicenter, cross-sectional EPOS [27], with the principal aim to examine the association between genetic variations and opioid efficacy on cancer pain relief. Patients were eligible if they had verified malignant disease, were aged $18 years, and were scheduled with opioid treatment for moderate to severe pain for at least 3 days.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Whole blood samples were obtained and DNA extraction and SNP analyses were performed as previously described [27]. Individuals with a minimum allele frequency of less than 5% or in violation with the Hardy-Weinberg equilibrium (chi-square test, p , .0005) were excluded [36].…”
Section: Polymorphism Analysesmentioning
confidence: 99%
“…A large sample study has indicated that none of 112 SNPs in the 25 candidate genes showed significant associations with opioid dose (15); however, this study lacked clarity regarding the doses of concomitant analgesics, the dose determination of opioids, and the high average total dose of morphine of 90 mg/day. Despite this dose, residual pain was relatively high (pain NRS in the past 24 h, 3.20±2.10 subsequent to analgesic use and no data for pain NRS prior to analgesic use) (15). This suggests a high proportion of refractory pain.…”
Section: Discussionmentioning
confidence: 93%
“…A large sample study has indicated that none of the 112 single nucleotide polymorphisms (SNPs) in 25 candidate genes demonstrated significant associations with opioid dose (15); however, the quantity of concomitant analgesics [non-steroidal anti-inflammatory drugs (NSAIDs) and acetaminophen] and the method for dose determination of opioids remain unclear. Furthermore, the mean Brief Pain Index (16) following treatment was relatively high (15).…”
Section: Introductionmentioning
confidence: 99%
“…Examining 123 single nucleotide polymorphisms (SNPs) from the most relevant candidates, 9 showed significant association with opioid dosage. 1 Based on DNA pools from 'good' and 'poor' opioid responders, a novel set of 17 SNPs was identified, explaining as much as 25% of the phenotypic variation in a regression model. 2 A major challenge in the gene studies was to agree upon a valid system for classification (categorization) of cancer patients with pain, or in other words, how to phenotype the patient.…”
mentioning
confidence: 99%